Model calculation of a solar assisted system for a malt kiln - Hauner, Manfred; Eichhorn, Karl; Vearasilp, Suchada; Sa-nguansak Thanapornpoonpong, Sa-nguansak; Changrue, Viboon (BrewingScience, 2019)
The kilning of green malt requires large amounts of thermal energy which is nowadays mainly based on fossil fuels. In a standard state-of-the-art malting plant in South-East Asia, 800 kWh is needed for one tonne of malt. At such a high level of energy usage, it is obvious that more sustainable energy sources must be investigated. The purpose of these studies is, therefore, to investigate a solar assisted malt kiln with the maximum usage of solar energy and to validate its performance by a model calculation. With a pilot plant in Vietnam, trials have been executed successfully and the first solar malt, kilned with thermal energy solely from the sun were produced. Furthermore, trials were carried out with conventional and solar heat for maximum energy conservation. The finished malt from all trials was then tested in the industrial malt laboratory and qualified as brewing malt. Starting from the design of the malt kiln, the energy demand and air flow, the dimensioning of the solar circuit for the solar malt kiln, the savings compared with the usage of fossil energy was conducted in a computer based model calculation. The savings from solar heat investigated as the representational case for 360 tonnes of barley in Vietnam can be generated at between 99.2 % and 59.8 %. Thus a larger impact can be identified with the rainy season in South-East Asia. Due to changing the solar contribution and heat demand over the seasons, for the industrial scale it will be always essential to have 100 % backing with a conventional heating. The CO2 footprint savings were calculated as annual average of 137.63 kg CO2 per tonne of finished malt for savings of natural gas and 150.14 kg CO2 for savings of fuel oil. The results generated from the model calculation in these studies demonstrate huge potential for the malting industry.